2019
DOI: 10.1007/s10926-019-09866-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vocational Re-training on Employment Outcomes Among Persons with Disabilities in Germany: A Quasi-Experiment

Abstract: Purpose To investigate how completing vocational re-training influenced income and employment days of working-age people with disabilities in the first 8 years after program admission. The investigation also included the influence of vocational re-training on the likelihood of receiving an earnings incapacity pension and on social security benefit receipt. Methods This retrospective cohort study with 8 years follow up was based on data from 2399 individuals who had completed either a 1-year vocational re-train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…Therefore, four years after the start of VR, when most participants should have finished VR -even if other programmes followed training -, the employment prospects of training participants exceeded those of non-participants. Similar positive employment outcomes after training participation were also found for the unemployed [12] and for rehabilitants supported by the SPI [4].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Therefore, four years after the start of VR, when most participants should have finished VR -even if other programmes followed training -, the employment prospects of training participants exceeded those of non-participants. Similar positive employment outcomes after training participation were also found for the unemployed [12] and for rehabilitants supported by the SPI [4].…”
Section: Discussionsupporting
confidence: 70%
“…No general effect of training was identified. In order to determine the effect of training participation compared to discontinued training, another recent study [4] identified a positive employment and income effect for those who completed their training. Despite the existence of these studies, they are difficult to compare to our study.…”
Section: Current State Of Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from unemployment contexts (Hirschenauer 2013 ), vocational rehabilitation (Hetzel and Streibelt 2016 ; Reims and Tophoven 2018 ; Echarti et al 2020 ) and medical rehabilitation (Kaluscha et al 2013 ) indicate that the regional labour market decreases RTW. In these contexts, the labour market is operationalized either indirectly via assignment to a regional unit (Leinonen et al 2019 ; Echarti et al 2020 ) or directly via characteristics of the regional labour market, such as the unemployment rate (Kaluscha et al 2013 ; Hetzel 2015 ; Hetzel and Streibelt 2016 ; Reims and Tophoven 2018 ). In our opinion, there is evidence for vocational rehabilitation (Hetzel and Streibelt 2016 ; Reims and Tophoven 2018 ; Echarti et al 2020 ), but not for medical rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Propensity score matching has been a commonly used technique (16)(17)(18). A recent German study comparing vocational training program participants and drop-outs found that the participants had more working days and higher earnings, less days on social security benefits and lower probability of receiving earnings incapacity pension (19). Another German study, focusing on the unemployed, found better employment prospects among persons accepted to VR than among rejected applicants (20).…”
mentioning
confidence: 99%